The stability of flow with suspended sediment in an inclined channel of movable bed - Chung, Dang Huu (Vietnam Journal of Mechanics, 1991)
In this work the author has studied the stability of flow with suspended sediment in an inclined channel of movable bed at different stages of flow. The obtained result shows that when the flow with suspended sediment is at the stage of deposition or erosion then the critical inclined angle is less than that one of homogeneous flow, e. g., the flow with suspended sediment is earlier unstable. If the exchange between suspended sediment and bed-load doesn’t occur, the existence of sediment will not act on the condition of stability. In particular when C0 = 0 the classical result is obtained. The author would like to thank to Prof-Doctor Nguyen Van Diep for useful helping.